Asymptotic Methods in the Theory of Perforated Membrane of Nonhomogeneous Structure - I.V. Andrianov; G.A. Starushenko (Engineering Transactions, 1995)
Homogenization equations are constructed for perforated membranes. Asymptotic methods are used for solving the cell problem.